Nanoemulsions as a Promising Carrier for Topical Delivery of Etodolac: Formulation Development and Characterization - Samet Özdemir; Burcu Üner; Alptuğ Karaküçük; Burak Çelik; Engin Sümer; Çetin Taş (MDPI AG, 2023)
This research primarily focuses on the development of innovative topical nanoemulsions for etodolac, aimed at surmounting its inherent limitations. The preparation of etodolac nanoemulsions is accomplished through a combination of high shear homogenization and ultrasonication methods. The optimization of the formulation components is systematically conducted using the design of experiments methodology. The droplet size (DS), polydispersity index (PDI), and zeta potential (ZP) of the optimized formulation were assessed using the differential light scattering (DLS) technique. Surface morphology examinations were conducted using electron microscopy, while interactions between excipients and the drug were analyzed through FTIR analysis. Additionally, in vitro release and ex vivo permeability studies were carried out. Furthermore, anti-inflammatory activity was evaluated in the context of a carrageenan-induced paw edema model in rats. The DS, PDI, and ZP of the optimal formulation were 163.5 nm, 0.141, and −33.1 mV, respectively. The in vitro release profile was assessed as a sustained release by following a non-Fickian drug transport. The flux of etodolac nanoemulsions and coarse dispersions were 165.7 ± 11.7 µg/cm2 h and 59.7 ± 15.2 µg/cm2 h, respectively. Enhanced edema inhibition was observed at 13.4%, 36.5%, and 50.65% for the 6th, 8th, and 24th hours, respectively. Taken together, these results confirmed that nanoemulsions are promising carriers for the topical delivery of etodolac.